2017
DOI: 10.3390/admsci7020013
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of Almutairi’s Critical Cultural Competence Scale

Abstract: This paper reports on a psychometric study conducted to explore the factor structure and refine the Critical Cultural Competence Scale (CCCS). Critical Cultural Competence (CCC) functions to promote the safety, equity, and well-being of patients, their families, and health care professionals. The development process of this measurement scale was systematic and iterative, and included generating a pool of potential items based on the theoretical definitions of CCC. In this study, conducted with a sample of 170 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
(41 reference statements)
0
15
1
Order By: Relevance
“…The critical empowerment subscale had the highest scores among all subscales in this study, although it was still lower than the findings of Almutairi and Dahinten (2017). This suggested that China's clinical nurses lacked critical empowerment.…”
Section: Discussioncontrasting
confidence: 89%
“…The critical empowerment subscale had the highest scores among all subscales in this study, although it was still lower than the findings of Almutairi and Dahinten (2017). This suggested that China's clinical nurses lacked critical empowerment.…”
Section: Discussioncontrasting
confidence: 89%
“…The 43-item CCCS is a self-report questionnaire with four subscales: Critical Awareness (12 items), Critical Knowledge (seven items), Critical Skills (seven items), and Critical Empowerment (17 items) (Almutairi & Dahinten, 2016). Responses are measured on a 7-point Likert-type scale, anchored from strongly disagree (1) to strongly agree (7) for most of the items, and from never (1) to always (7) for the items that measure how often certain events have happened.…”
Section: Methodsmentioning
confidence: 99%
“…The Critical Cultural Competence Scale (CCCS) was then developed to measure health care providers’ self-reports of critical cultural competence within a multicultural context. The CCCS was developed through a systematic and iterative process that included deconstructing the theoretical components of the critical cultural competence model into a number of representative items, expert review for content validity, and informal pilot studies with a multicultural group of graduate nursing students in Canada and a multicultural group of staff nurses in Saudi Arabia (Almutairi & Dahinten, 2016). Exploratory factor analysis (EFA) supported a four-factor solution consistent with the theoretical underpinnings of the subscales: Critical Awareness (12 items), Critical Knowledge (seven items), Critical Skills (seven items), and Critical Empowerment (17 items).…”
Section: A Model Of Critical Cultural Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Although cultural competency training for medical professionals has been shown to help reduce provider bias and improve communication in limited research [25], the narrow focus on list-based 'characteristics,' which are presumed to be easily identified based on race/ethnicity alone, may perpetuate the very stereotypes which cultural awareness seeks to avoid [26]. Moreover, cultural competency often overlooks the fact that western biomedicine and its institutionalized delivery is a culture of its own, one that it is often assumed to be normative and just [27]; medical students are asked to learn about 'others' (often the minority) but not so much to reflect upon the cultural 'us' (biomedicine) and the privileged place from which that learning of 'others' takes place [28,29].…”
Section: Patient-centered Care Sharing and Advocacymentioning
confidence: 99%